Contrastive Analysis of Tabe Politeness Speech Acts in Bugis and Sumimasen in Japanese (Pragmatic Study) - Putri Bintang Pratiwi Harahap; Kartyka Nababan (Universitas Muhammadiyah Yogyakarta, 2024)
This research investigates the level of politeness exhibited by Tabe in Bugis and Sumimasen in Japanese. The researchers do a contrastive analysis to examine the differences and similarities between Tabe in Bugis and Sumimasen in Japanese, which encompasses the act of begging and the pragmatic aspect of politeness. This research uses a contrastive descriptive qualitative methodology, in which the data consists of elaborate qualitative information rather than numerical values. This data is examined by using two distinct approaches, specifically descriptive and contrastive data analysis. The findings of this investigation in the term